2020
DOI: 10.3389/fbioe.2020.00998
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of the Locomotor Circuitry in Children With Cerebral Palsy

Abstract: The first years of life represent an important phase of maturation of the central nervous system, processing of sensory information, posture control and acquisition of the locomotor function. Cerebral palsy (CP) is the most common group of motor disorders in childhood attributed to disturbances in the fetal or infant brain, frequently resulting in impaired gait. Here we will consider various findings about functional maturation of the locomotor output in early infancy, and how much the dysfunction of gait in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 208 publications
(273 reference statements)
2
18
0
Order By: Relevance
“…For the reasons noted above our interventional strategy as presented has been focused functionally on the necessity of realigning the sensorymotor connectivity to accommodate to normal gravitational vectors. Theoretically, to regain a normal supraspinal-spinal connectivity to earth's gravitational forces, the earlier maladaptive state that was learned postnatally to sustain equilibrium while in an abnormal state, must be re-transformed to achieve a normal translation of sensory input in a 1G environment (Smith and Gorassini, 2018;Cappellini et al, 2020).…”
Section: The Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…For the reasons noted above our interventional strategy as presented has been focused functionally on the necessity of realigning the sensorymotor connectivity to accommodate to normal gravitational vectors. Theoretically, to regain a normal supraspinal-spinal connectivity to earth's gravitational forces, the earlier maladaptive state that was learned postnatally to sustain equilibrium while in an abnormal state, must be re-transformed to achieve a normal translation of sensory input in a 1G environment (Smith and Gorassini, 2018;Cappellini et al, 2020).…”
Section: The Problemmentioning
confidence: 99%
“…We reasoned that we could do this by maximizing the dominance of proprioception and the spinal networks that translate this sensory input and minimizing the pathology of the brain, in controlling posture and locomotion. Cappellini et al (2016Cappellini et al ( , 2020 noted how much the dysfunction of gait in children with CP can be related to spinal neuronal networks vs. supraspinal dysfunction. A more thorough knowledge about pattern generation circuitries in infancy may improve our understanding of developmental motor disorders, highlighting the necessity for regulating the functional properties of abnormally developed neuronal locomotor networks as a target for early sensorimotor rehabilitation.…”
Section: Solutionmentioning
confidence: 99%
“…The motor dysfunction of CP is one of the most common causes of disability in infants, of which the injury of the developing brain affects multiple networks of the CNS, including corticospinal tract (60) and the physiological state of the spinal cord (61,62).…”
Section: Crawling Intervention To Promote the Locomotor Function In Early Infancymentioning
confidence: 99%
“…The elements observed in infancy are not discarded but instead become adapted, in parallel with changes in locomotion biomechanics (Dominici et al, 2011 ; Cappellini et al, 2020 ; Cheung et al, 2020 ; Dewolf et al, 2020 ) and with the neural maturation of central pathways. Interestingly, Sylos-Labini et al ( 2020 ) showed that the spatiotemporal organization of locomotor output observed during spontaneous movements also anticipates some features of walking development.…”
Section: The Pivotal Role Of Experience and Maturation On The Developmentioning
confidence: 99%